Contemporary Islamic Studies in Japan: Integration Within Area and Cultural Studies at Higher Education Institutions - Mia Fitriah Elkarimah; Husni Mubarak; Muhammad Ali Adha (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
This study examines the integration of Islamic studies within Japanese higher education, emphasizing its distinctive institutional and epistemological framework in comparison with theological models in Muslim-majority and Western contexts. Using qualitative document analysis and content analysis, the study focuses on four leading Japanese universities: The University of Tokyo, Kyoto University, Waseda University, and Sophia University. The primary data comprise official curricula, course syllabi, program descriptions, and departmental guidelines collected from university websites between 2010 and 2023, while secondary data include academic journals, scholarly books, and research reports. The findings indicate three distinctive features of Japanese Islamic studies: an interdisciplinary and empirical orientation that combines history, sociology, anthropology, political science, and economics; an inclusive and pluralistic approach that promotes diversity and coexistence within a secular context; and a diplomatically engaged and globally oriented framework that links academic inquiry with international cooperation and interreligious dialogue. This model reflects Japan’s dual concern with understanding global Islamic dynamics and responding to the needs of its growing Muslim population. The study argues that the Japanese model offers a significant contribution to global Islamic studies by demonstrating how secular institutions can conduct objective religious research without normative agendas while fostering cross-cultural understanding in multicultural settings.